2006
DOI: 10.1210/en.2006-0252
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits Glucocorticoid Receptor Nuclear Translocation in Mouse Thymocytes

Abstract: The antiapoptotic effect of melatonin (MEL) has been described in several systems. In particular, MEL inhibits glucocorticoid-mediated apoptosis. Our group previously demonstrated that in the thymus, MEL inhibits the release of Cytochrome C from mitochondria and the dexamethasone-dependent increase of bax mRNA levels. In this study we analyzed the ability of MEL to regulate the activation of the glucocorticoid receptor (GR) in mouse thymocytes. We found that even though the methoxyindole does not affect the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 61 publications
(64 reference statements)
2
45
0
2
Order By: Relevance
“…The mechanisms whereby melatonin influences apoptosis have not yet been clarified, although different options have been suggested. Melatonin has been found to inhibit glucocorticoidand hydroxyl radical-induced thymocytes apoptosis, through its anti-oxidative effects and inhibiting glucocorticoid receptor nuclear translocation in thymocytes [41,66,67]. On the other hand, this molecule can protect the thymus by modulating zinc levels [68 -70], necessary for the active form of thymulin and other functions [71], and by increasing some thymic peptides production [42].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms whereby melatonin influences apoptosis have not yet been clarified, although different options have been suggested. Melatonin has been found to inhibit glucocorticoidand hydroxyl radical-induced thymocytes apoptosis, through its anti-oxidative effects and inhibiting glucocorticoid receptor nuclear translocation in thymocytes [41,66,67]. On the other hand, this molecule can protect the thymus by modulating zinc levels [68 -70], necessary for the active form of thymulin and other functions [71], and by increasing some thymic peptides production [42].…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications proposed that melatonin prevents GR nuclear translocation in a tissue specific dependent manner after glucocorticoid treatment [27]; however, its role on hippocampal cells is currently unknown. We studied the ability of melatonin to prevent GR nuclear translocation induced by DEX.…”
Section: Melatonin Prevents Nuclear Translocation Of Glucocorticoid Rmentioning
confidence: 99%
“…These actions are mediated by reductions in mRNA levels for GR in these cells [26]. More recently, it was found that even though melatonin does not affect protein levels or the binding activity of GR, it reduces its nuclear translocation by blocking its dissociation from the heat shock protein (Hsp90) in thymocytes [27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies report an antiapoptotic effect of melatonin. This anti-apoptotic effect may be associated to its antioxidative action (Sainz et al, 1999;Espino et al, 2011), to its inhibition of the nuclear translocation of glucocorticoid receptors (Sainz et al, 1999;Presman et al, 2006), to its modification of zinc levels (Mocchegiani et al, 1994) or to up-and downregulation of gene expression of Bcl-2 and Bax protein respectively (Jing et al, 2014). Espino et al (2010) moreover found that in human neutrophils melatonin inhibited apoptosis via reduction of caspase-9 and -3 activity as well as through reduction of the mitochondrial permeability to ions (Espino et al, 2010).…”
mentioning
confidence: 99%